Capital Punishment and (in)Justice - Wahyuni, Ribut Tirto (Universitas Negeri Semarang, 2021)
Indonesia is a legal state that upholds justice based on Article 1 paragraph 3 of the 1945 amendment. However, the legal condition in Indonesia is currently heavily criticized by the people, especially the small people. Laws in Indonesia are often called blunt-sharp laws that are triggered by the weakness of law enforcement in Indonesia. The condition of justice law in the increasingly bad state of Indonesia greatly affects the health and democratic forces in Indonesia. Failure to realize justice through law in Indonesia must be immediately addressed for the creation of a just state of justice as stipulated in the content of Pancasila. Law enforcement in Indonesia is not in accordance with Article 1 Paragraph 3 of the 1945 Amendment of Amendment which states that Indonesia is a State of law. This study aims to analyze the capital punishment in the context of justice and fairness, as well as human rights perspective.